2013
DOI: 10.1158/1078-0432.ccr-12-3027
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Downregulates TRAIL Expression in Human Peripheral Monocytes via an Egr-1–Dependent Pathway

Abstract: Purpose: To investigate the potential link between C-reactive protein (CRP), a known biomarker of acute and chronic inflammation, and TRAIL, a cytokine which plays a key role in the immune-surveillance against tumors.Experimental Design: Primary normal peripheral blood mononuclear cell (PBMC) and CD14 þ monocytes were exposed to recombinant CRP (1-10 mmol/L). TRAIL expression was analyzed by ELISA and/or by quantitative real-time PCR (qRT-PCR). In parallel, the potential role of the transcription factor Egr-1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 56 publications
(58 reference statements)
4
24
1
Order By: Relevance
“…In agreement with a previous study [25], uric acid, total cholesterol, and triglycerides were higher in subjects belonging to the III TRAIL tertile. In contrast with a previous report [26], hemoglobin, creatinine, albumin, HDL and LDL cholesterol, fasting glucose and hsCRP were not associated with serum TRAIL levels. Concerning comorbidities, the prevalence of COPD was inversely associated with TRAIL levels, as previously reported [27].…”
Section: Resultscontrasting
confidence: 99%
“…In agreement with a previous study [25], uric acid, total cholesterol, and triglycerides were higher in subjects belonging to the III TRAIL tertile. In contrast with a previous report [26], hemoglobin, creatinine, albumin, HDL and LDL cholesterol, fasting glucose and hsCRP were not associated with serum TRAIL levels. Concerning comorbidities, the prevalence of COPD was inversely associated with TRAIL levels, as previously reported [27].…”
Section: Resultscontrasting
confidence: 99%
“…In line with these results, a marginally positive correlation between TRAIL and apelin, an anti-inflammatory adipokine, was also observed. These results further support the previously described anti-inflammatory role of TRAIL [17]. …”
Section: Discussionsupporting
confidence: 92%
“…Although TRAIL/TRAILR system is generally considered to be a component of the cell anti-tumorigenic activity, its physiopathological role is broader than originally thought (Di Pietro & Zauli 2004). In particular, the ability of TRAIL to suppress inflammatory reactions has been demonstrated in a variety of studies (Li et al 2012, Marcuzzi et al 2012, Keuper et al 2013, Secchiero et al 2013, Walczak 2013. The second major finding of our study was that recombinant TRAIL, used at concentrations comparable to those found in seminal plasma (10 ng/ml), significantly increased the overall survival of capacitated spermatozoa.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, the presence of TRAIL in seminal plasma has never been evaluated. It should also be taken into consideration that a growing number of studies from different groups of investigators have shown that TRAIL displays anti-inflammatory activity (Li et al 2012, Marcuzzi et al 2012, Keuper et al 2013, Secchiero et al 2013, Walczak 2013. On these bases, the aim of our present study was i) to analyze the presence and the levels of soluble TRAIL in the seminal samples and the surface expression of TRAIL receptors in the sperm cellular fraction and ii) to evaluate the potential biological activity of soluble TRAIL, by assessing the in vitro response of spermatozoa in terms of vitality/survival and motility upon exposure to recombinant TRAIL.…”
Section: Introductionmentioning
confidence: 99%